Efficacy and safety of golimumab in Crohn's disease: a French national retrospective study. Issue 11 (13th October 2017) - Martineau, C.; Flourié, B.; Wils, P.; Vaysse, T.; Altwegg, R.; Buisson, A.; Amiot, A.; Pineton de Chambrun, G.; Abitbol, V.; Fumery, M.; Hébuterne, X.; Viennot, S.; et al.
Summary: Background: Anti‐tumour necrosis factor (TNF) agents have improved the care of Crohn's disease (CD). After the first anti‐TNF discontinuation, it is possible to switch to another anti‐TNF. Three anti‐TNF agents are available for ulcerative colitis (infliximab, adalimumab and golimumab), but only the first 2 have been approved for CD because golimumab has not been studied for this indication. Aim: To report the efficacy and safety of golimumab in CD. Methods: Crohn's disease patients who received golimumab were identified in 12 French tertiary centres and were retrospectively analysed. The primary endpoint was the duration of golimumab treatment before escalation or discontinuation. The clinical response was defined as a decrease of more than 3 points in the Harvey‐Bradshaw index or by global physician assessment. Results: One hundred and fifteen patients were included. The golimumab treatment duration was 9.8 months (0.55‐44), and 48.7% of the patients were still under treatment at the end of follow‐up. Clinical response was observed in 55.8% of the patients after a mean duration of 3.8 months. The probability of remaining under treatment without escalation at 6, 12 and 24 months was 54.6%, 34.9% and 19.3% respectively. In multivariate analysis, discontinuation of the first anti‐TNF agent due to intolerance (odds ratio, OR = 2.16; 95% CI, confidence interval [1.25‐3.86]; P = .005) and co‐immunosuppression for more than 6 months (OR = 3.98; 95% CI [2.3‐7.1]; P < .0001) were predictive factors of efficacy. Six per cent of the patients discontinued treatment due to intolerance. Conclusion: After failure of infliximab or adalimumab for Crohn's disease, golimumab was safe and seemed beneficial in half of the patients.